Childhood factors associated with muscular strength trajectories between childhood and mid-adulthood - Fraser, BJ; Blizzard, L; Cleland, V; Buscot, M-J; Dwyer, T; Schmidt, MD; Venn, AJ (Wolters Kluwer, 2022)
Purpose: To promote greater muscular strength across the life course and, in turn, help improve long-term health outcomes, strategies aimed at increasing muscular strength are required. To inform these strategies, this study identified childhood factors associated with muscular strength trajectories.